Synchronous and Asynchronous Learning for Students with Disability at Universitas PGRI Yogyakarta: Challenges and Implementation. - Fatmawati, Dwi Putri; Harjana, Ramdhan; Suminar, Yulian Agus (Jurnal Pendidikan Kebutuhan Khusus, 2025)
This study aims to investigate the implementation of synchronous and asynchronous learning for students with disabilities at Universitas PGRI Yogyakarta (UPY). Employing a qualitative approach with a descriptive method through a case study design, the data analysis involved data reduction, data presentation, and conclusion drawing and verification, with research participants being students with disabilities at UPY. The implementation of synchronous and asynchronous learning at UPY for students with disabilities received special attention due to their distinct learning conditions, utilizing various platforms such as Zoom, Google Meet, WhatsApp Group, UPY E-learning, YouTube, and Google Classroom. Each platform has its strengths and weaknesses. Conference-based platforms enable direct learning akin to face-to-face instruction but require stable internet connections and adequate devices. This study reveals that students with special learning needs at UPY utilize various online platforms, with Google Classroom and Zoom being the dominant media. Although these platforms are beneficial, most respondents still face technical and accessibility challenges. Proposed solutions emphasize the provision of accessible learning materials, network improvements, and greater learning flexibility.